2022
DOI: 10.3390/ma15238607
|View full text |Cite
|
Sign up to set email alerts
|

Printability, Thermal and Compressive Strength Properties of Cementitious Materials: A Comparative Study with Silica Fume and Limestone

Abstract: Over the past decade, 3D printing in the construction industry has received worldwide attention and developed rapidly. The research and development of cement and concrete products has also become quite well-established over the years, while other sustainable materials receive considerably lower attention in comparison. This study aims to investigate the influence of the two most commonly used sustainable cementitious materials i.e., silica fume and limestone powder, on printability, thermal and mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Srinivas et al [11] manufactured ternary cements by mixing Portland cement, coal fly ash, and silica fume or limestone powder to assess their rheological properties, and they found that their enhanced buildability was linked to their static yield stress. Therefore, silica fume and limestone, ranging from 5% to 10% with higher static yield stress, enhanced the buildability and reduced the anisotropic mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Srinivas et al [11] manufactured ternary cements by mixing Portland cement, coal fly ash, and silica fume or limestone powder to assess their rheological properties, and they found that their enhanced buildability was linked to their static yield stress. Therefore, silica fume and limestone, ranging from 5% to 10% with higher static yield stress, enhanced the buildability and reduced the anisotropic mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The highest increase in thixotropic behavior compared to the control mixture was obtained in the SF-6% and SF-9% mixture and the A thix method. In a similar study involving SF by [ 55 ], it was reported that SF has an optimum usage rate on its rheological properties. It was declared by the authors that substituting up to 10% of cement with SF increases the buildability of 3D printable concrete mixtures by providing higher SYS without affecting their extrudability.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the use of SF significantly increases the height change caused by DS at the early ages [ 73 ]. In a study conducted by [ 55 ], the effect of changing the SF usage rate on the CS of 3D printable concrete mixtures was examined. It was determined that the CS values of mixtures containing 5% and 10% SF were lower than the control mixture.…”
Section: Resultsmentioning
confidence: 99%
“…It can also reduce the heat of hydration and mitigate the risk of thermal cracking. However, its use may require adjustments to the mix design and printing parameters [67,175].…”
Section: Silica Fumementioning
confidence: 99%
“…This can cause tearing defects in the final printed layer [59]. The literature shows that the addition of cement content, nano clay [60,61], fiber content [62][63][64][65], silica fume [66,67], and fly ash [68][69][70][71] increases the yield strength of the concrete mix for printing purposes. Still, at the same time, they decrease the extrudability of the printable mix.…”
Section: Introductionmentioning
confidence: 99%